Internationalization of companies in Poland from the micro and small enterprise sector – the essence, forms, methods - Glinkowska-Krauze, Beata (Metody i techniki zarządzania. Inspiracje dla teorii i praktyki, 2020)
The paper presents selected issues at ways and forms of internationalization of micro and small enterprises in Poland. It includes the results of research made in the years 2013–2018 on a sample of 105 intentionally selected enterprises. The research methodology was presented in the introduction. The first part explains the essence of internationalization of enterprises in the context of the globalization process. The second part presents selected results from the tests performed. The study ends with conclusions, which concern the methods and forms of internationalization of the surveyed enterprises.